Hak imunitas bagi pejabat Komisi Pemberantasan Korupsi (KPK): Sebuah model usulan - Alfons Zakaria; Ardi Ferdian; Karna Rediyan Syahputra; Azahlia Umar (Komisi Pemberantasan Korupsi, 2023)
Attacks against officials of the Corruption Eradication Commission (KPK) often happen. The attacks show that there is an attempt to hinder the progress of corruption cases being handled by the KPK or perhaps to take revenge. Therefore, in carrying out their duties, officials of KPK should receive legal protection, namely limited immunity rights. The limited immunity rights are not new in Indonesia; the law has granted it to several state institutions/agencies. The purpose of this paper is to offer a model for the regulation of limited immunity rights for the KPK. This paper proposes a model of limited immunity rights for KPK leaders, investigators,r and public prosecutors within the scope of carrying out their duties and exercising their authorities. The proposed model stipulates that KPK officials cannot be interrogated, arrested, detained, prosecuted, or sued when occupying their positions. However, the rights to immunity is limited only to the period of occupying a position at the KPK and does not apply if KPK officials receive severe sanctions for ethical violations or commit special crimes.